Kecanggihan Teknologi Informasi, Skill, Pengalaman Kerja, Kompleksitas Tugas pada Efektivitas Sistem Informasi Akuntansi - Paramitha, Febby Dwi; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
This research aims to determine the influence of information technology sophistication, skills, work experience, and task complexity on the effectiveness of the accounting information system in the South Kuta District Village Credit Institution. The sample used was 85 employees who implemented an accounting information system. Samples were taken using the purposive sampling method. The analysis technique applied is multiple linear regression. The findings show that the sophistication of information technology, skills, work experience and task complexity have a positive influence on the effectiveness of the accounting information system in the South Kuta District LPD. The implications of this research for the LPD are that it is able to provide additional information regarding the factors that influence the effectiveness of the accounting information system, so it is hoped that it will be useful in increasing the effectiveness of the accounting information system in the South Kuta District LPD. Keywords: Accounting Information System; Information Technology Sophistication; Skills; Work Experience; Task Complexity.